Polychlorinated biphenyls in a grassland food network: Concentrations, biomagnification, and transmission of toxicity - Te, Bu; Yiming, Liu; Tianwei, Li; Huiting, Wang; Pengyuan, Zhao; Wenming, Chen; Jun, Jin (The Science of the total environment, 2020)
The production of polychlorinated biphenyls (PCBs) is prohibited by the Stockholm Convention in 2001, but the unintentionally produced PCBs are still continuously discharged into the environment. In this study, the distributions, biomagnification and toxicity amplification in a grassland food network (including inorganic environment, animals and vegetation) were investigated. PCB concentrations in various samples were determined, and PCBs appeared to be enriched as the trophic level increased. The PCB concentrations in the inorganic environment samples ranged from below the detection limit to 0.329 ng g−1, and the PCB concentrations in vegetation were 0.0829–4.45 ng g−1. The PCB concentration in snake subcutaneous fat (8.74 ng g−1 lipid weight) was higher than the concentrations in other animal samples, and the next highest concentration was found in yellow weasel muscle (7.31 ng g−1 lipid weight). Biomagnification factors were calculated for different PCBs and different organisms. Biomagnification was most obvious for organisms at the top of the food chain (the snake/mouse biomagnification ratio was >1000). The PCB-126 toxic equivalent concentration increased markedly as the trophic level increased. The toxic equivalent concentrations were 1200 times higher for high trophic level biota than low trophic level biota. PCB-169 had the highest toxic equivalent concentrations for the animal hair samples (0.00001 pg toxic equivalents g−1). However, PCB-81 had the highest toxicity equivalent concentrations for the herdsmen hair samples. PCBs found at relatively low concentrations and low toxic equivalent concentrations at low trophic levels can be biomagnified as they are transferred through the food chain and can reach high actual and toxic equivalent concentrations at high trophic levels. [Display omitted] •PCBs appeared to be enriched as the trophic level increased.•Snake/quarry had BMFs as high as 5000 for PCB-114, -156, and 169.•Up-PCBs (PCB-126, 169) had the highest TEQ concentrations in the organisms.